2014
DOI: 10.1007/s10384-014-0318-4
|View full text |Cite
|
Sign up to set email alerts
|

Preserve the (intraocular) environment: the importance of maintaining normal oxygen gradients in the eye

Abstract: Oxygen levels in the eye are generally low and tightly regulated. Oxygen enters the eye largely by diffusion from retinal arterioles and through the cornea. In intact eyes, oxygen from the retinal arterioles diffuses into the vitreous body. There is a decreasing oxygen gradient from the retina to the lens, established by oxygen consumption by ascorbate in the vitreous fluid and lens metabolism. Age-related degeneration of the vitreous body or removal during vitrectomy exposes the posterior of the lens to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…Thus, understanding the processes that control oxygen transport, concentration, and distribution in the lens are very important. Oxygen consumption is necessary to maintain a low oxygen concentration inside the eye lens; otherwise the concentration of oxygen would be equal to that outside the lens (Beebe et al, 2014; Siegfried et al, 2010). Mitochondrial respiration occurring in the outer layers of cortical fiber cells (not yet mature and containing organelles, including mitochondria) accounts for approximately 90% of oxygen consumption by the lens (McNulty et al, 2004), ensuring a low oxygen concentration in the lens nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding the processes that control oxygen transport, concentration, and distribution in the lens are very important. Oxygen consumption is necessary to maintain a low oxygen concentration inside the eye lens; otherwise the concentration of oxygen would be equal to that outside the lens (Beebe et al, 2014; Siegfried et al, 2010). Mitochondrial respiration occurring in the outer layers of cortical fiber cells (not yet mature and containing organelles, including mitochondria) accounts for approximately 90% of oxygen consumption by the lens (McNulty et al, 2004), ensuring a low oxygen concentration in the lens nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have shown that vitrectomy and cataract surgery significantly increase IOP and the risk of developing POAG, 55,56 which is due to exposure of the TM and SC to a higher level of oxygen causing oxidative damage to these tissues. 57,58 We demonstrated in vitro in an aging model of hyperoxia that it altered eNOS and its phosphorylation status and resulted in reduced NO production. Together with our previous data 39,49 showing that hyperoxia can cause increased resistance at the level of SC, these findings suggest that vitrectomy and phacoemulsification and the related oxygen concentration elevation could cause increased IOP by damaging SC.…”
Section: Discussionmentioning
confidence: 99%
“…While one could argue that nothing new was to be expected concerning the protective role of GSH in the lens, our interest in GSH homeostasis in the lens was rekindled with the unexpected finding that lenticular GSH levels were not completely suppressed in the LEGSKO mouse in spite of complete absence of γ-glutamylcysteine ligase(Fan et al, 2012). This issue, which is the subject of intense investigation in our laboratory, is closely linked to lenticular ascorbate metabolism and cataractogenesis and the work of David Beebe who has pioneered the importance of the vitreous as a source of oxidative stress to the lens(Beebe et al, 2014; Holekamp et al, 2005; Li et al, 2013b; Shui et al, 2009). These paradigm shifting studies inspired us to study lens biology in connection not only to the aqueous humor but also to the vitreous humor.…”
Section: Introductionmentioning
confidence: 99%